Y = x + 6
y = -3x + 6
put the system of linear equations into standard form
x - y = -6
-3x - y = -6
solution:
x = 0
y = 6
Answer:
74
Step-by-step explanation:
(80+96+81+89+64)÷5 = 84
Used the formula to get the average of a number. Hope this helps
Answer:
<em>− 2sin(b) / cos(2b)</em>
Step-by-step explanation:
DIFFERENTIATE W.R.T. B is a different method entirely
We simply add together the numerators and set with 2cos
then keep this number and add to sinb and square it.
then repeat initial 2 + cosb ^2 but instead of multiplying its add.
Then set the whole division to -sin (2b) squared then +1
<em> − 2cos(b)(3(sin(b))^2+(cos(b))^2) / −(sin(2b)) ^2 +1 </em>